Potential categories of employment stress among rural college students and their relationship to employment psychology - Wu, Xinyue; Kim, Kyung Yee; Jian, Ziting (Frontiers in Psychology, 2024)
Background: Psychological problems related to employment are among the most common psychological problems faced by rural college students. Employment stress is an important factor affecting the development of psychological health in employees; thus, reducing employment stress can improve the psychological state of employment.Objective: This study aimed to understand the potential profiles of employment stress among rural college students to determine the relationship between different profiles and employment psychology.Methods: This study was conducted in a higher education institution in Qingdao, Shandong Province, China between June and December 2023, and 249 rural college students participated. The Employment Stress Scale and Employment Psychology Scale were used to collect the data. Data were analyzed using latent profile analysis, independent sample t-tests, and binary logistic regression analysis.The results showed that rural university students were categorized into low-level (49.80%) and high-level (50.21%) employment stress groups. There was a statistically significant difference between the employment psychology of rural college students in the low-and high-level groups (P < 0.001). Juniors/seniors were more likely to be classified in the high-level group (OR=0.477, P=0.011).Intervention programs should be developed and implemented to address the characteristics of employment stress among rural college students with different profiles to promote the healthy development of their attitudes toward employment.